The Influence of Financial Threat on Go-Jek Drivers' Willingness to Change Financial Behavior in Surabaya, Indonesia - Anastasia, Njo; Avila, Axel (SBM ITB, 2022)
Abstract. During the COVID-19 pandemic, Go-Jek drivers have experienced economic difficulties due to a decline in online orders from consumers. This decline and the fear of contracting the virus have prompted Go-Jek drivers to try various alternatives to be able to meet their daily necessities. This study aims to determine the effect of financial threat on the willingness to change financial behavior among Go-Jek drivers in Surabaya, Indonesia. Data was collected through a questionnaire distributed online using Google Forms, Instagram as well as offline, so that 100 respondents could be obtained. After the data was collected, it was processed through SEM-PLS to examine the relationship of economic hardship, debt, anxiety, and financial threat to willingness to change financial behavior. On the one hand, the results of the analysis show that debt and anxiety had a significant effect on financial threat, and that financial threat had a significant effect on the willingness to change financial behavior. On the other hand, they indicated that economic hardship did not have a significant effect on financial threat. Difficult financial conditions affected Go-Jek drivers' psychological conditions, and they had to be willing to change their financial behavior to survive; hence, psychological factors and financial knowledge have an influence on individuals in terms of their ability to make wise financial decisions.Keywords: Economic hardship, debt, anxiety, financial threat, willingness to change financial behaviorAbstrak. Selama pandemic COVID-19, driver Go-Jek mengalami kesulitan ekonomi disebabkan sulit mendapatkan pesanan secara online dari konsumen. Aktivitas pesanan online yang menurun serta ketakutan tertular virus mendorong driver Go-Jek untuk berusaha berbagai cara agar tetap dapat memenuhi kebutuhan hidupnya. Penelitian ini bertujuan untuk mengetahui pengaruh financial threat terhadap willingness to change financial behavior pada driver Go-Jek di Surabaya. Pengumpulan data dilakukan melalui kuesioner yang disebarkan secara online menggunakan google form, instagram serta offline, sehingga diperoleh 100 responden. Setelah data terkumpul, maka data diolah menggunakan SEM-PLS untuk menguji pengaruh economic hardship, debt, anxiety dan financial threat terhadap willingness to change financial behavior. Hasil analisis menunjukkan debt dan anxiety berpengaruh signifikan terhadap financial threat. Financial threat berpengaruh signifikan terhadap willingness to change financial behavior. Sebaliknya, economic hardship tidak berpengaruh terhadap financial threat. Kondisi keuangan yang sulit mempengaruhi kondisi psikologi driver Go-Jek, sehingga dibutuhkan kerelaan untuk mengubah perilaku keuangan agar tetap dapat bertahan, dimana faktor psikologi dan pengetahuan finansial memiliki pengaruh pada diri sendiri untuk dapat mengambil keputusan finansial dengan bijaksana.Katakunci: Economic hardship, debt, anxiety, financial threat, willingness to change financial behavior